Analisis Potensi Sebaran Mineral Logam Berdasarkan Data Anomali Magnetik - Bonefasius Hati Sanbein; Hadi Imam Sutaji; Bernandus (Sistem Informasi, 2022)
One of the the magnetic anomalies pattern and the layering of subsurface rock that are thought to be associated with metallic minerals has been done in Fatunisuan area, Miomaffo Barat District, Timor Tengah Utara Regency. Qualitative interpretation of the research results shows that the magnetic anomaly pattern at the study site is around -60 nT to 160 nT which is divided into low anomaly (-160 nT to 0 nT), moderate anomaly (0 nT to 100 nT) and high anomaly (100 nT to 100 nT). 160 nT). For the quantitative interpretation of the A-A1 incision, the B-B1 incision and the C-C1 incision to indicate that the rock with the greatest susceptibility value, namely limestone between 0.00127 cgs to 0.00791 cgs is thought to be associated with metalic minerals. The distribution of these limestones can be found dominantly in the southwest, west-southwest, northeast, east-northeast, west, west-northwest and southeast directions.